Embedded Al-Doped ZnO Grating Strips underneath MgNiO Photoconductor-Structured Ultraviolet Photodetectors. (30th August 2018) - Lee, Hsin-Ying; Lin, Chi-Wen; Lee, Ching-Ting
Abstract : By embedding high-conductive Al-doped ZnO grating strips underneath the MgNiO absorption layer, the photoconductor-structured ultraviolet photodetectors (UVPDs) were fabricated. When the MgNiO absorption layer was annealed at 500°C for 1 hour, the optical bandgap energy was 3.87 eV which corresponded to the cutoff wavelength of 320 nm of the fabricated UVPDs. The dark current of the UVPDs without and with Al-doped ZnO grating strips revealed a similar value of 0.9 μA and 1 μA, respectively. However, compared with the photoresponsivity of 3.0 A/W of the UVPDs without Al-doped ZnO grating strips, the photoresponsivity of the UVPDs with Al-doped ZnO grating strips was improved to 20.1 A/W at the wavelength of 320 nm.